Duration of storage influences the hemoglobin rising effect of red blood cells in patients undergoing major abdominal surgery. Issue 8 (17th April 2018) - Hunsicker, Oliver; Hessler, Katarina; Krannich, Alexander; Boemke, Willehad; Braicu, Ioana; Sehouli, Jalid; Meyer, Oliver; Pruß, Axel; Spies, Claudia; Feldheiser, Aarne
Abstract : BACKGROUND: After transfusion of senescent red blood cells (RBCs) a considerable fraction is rapidly cleared from the recipients' circulation. Thus, transfusion of senescent RBCs may be less effective in terms of increasing hemoglobin concentration ( c Hb) after transfusion. STUDY DESIGN AND METHODS: Data were retrospectively obtained in patients who underwent major abdominal surgery between 2006 and 2012. Patients were eligible if they received RBCs during surgery and had at least two arterial blood gas analyses performed. The primary endpoint was the increase of recipients' c Hb related to the transfusion of 1 unit of RBCs with respect to different storage periods. Four storage periods were defined according to the distribution of RBC storage of the study population. General estimating equation was used for calculation of the primary endpoint and to adjust for confounding variables. RESULTS: A total of 598 arterial blood gas samples from 120 patients, receiving 429 RBC units, were analyzed. Mean (±SD) RBC storage was 21 (±9) days. RBC storage duration and the increase in recipients' c Hb were inversely and gradually related; that is, the older the RBCs, the lower the increase in the recipients' c Hb after transfusion (storage < 12 days, Δ c Hb per unit RBCs +0.82 [95% confidence interval, 0.42‐1.21] g/dL, p  <  0.01; storage 12‐20 days, +0.66 [0.46‐0.86] g/dL, p  <  0.01; storage 21‐29 days, +0.56 [0.33‐0.79] g/dL, p  <  0.01; storage ≥30 days, +0.39 [0.07 to 0.71] g/dL, p  =  0.02). CONCLUSION: Transfusion of senescent RBCs increased c Hb less effectively than transfusion of fresher RBCs.